2022
DOI: 10.1371/journal.pone.0268041
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of neonatal near miss among neonates admitted to public hospitals in Southern Ethiopia, 2021: A case-control study

Abstract: Background Neonatal near-miss (NNM) cases refer to situations in which babies are on the verge of dying between the ages of 0 and 28 days due to severe morbidity that occurs during pregnancy, delivery, or extra-uterine life, but survive either by luck or due to high-quality health care. Identifying NNM cases and addressing their determinants is crucial for devising comprehensive and relevant interventions to tackle neonatal morbidity and mortality. Hence, this study aimed at finding out the determinants of NNM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
3
3
0
Order By: Relevance
“…In this study, exposed women who were treated after half an hour (faced delay three) in the hospital were more than six times more likely to have adverse perinatal outcomes than nonexposed women (AOR = 6.40, 95% CI: 1.5–27.54). This finding is similar to studies done in Malaysia [ 30 ], Brazil [ 25 ], India [ 31 ], Mozambique [ 32 ], and Ethiopia [ 33 ] in that adverse perinatal outcomes were highly linked to third delay. This could be explained by the dearth of qualified and skilled personnel, inadequate staff, limited supply of medicine and equipment, poor facility situations, and poor attitudes and care on the part of healthcare workers which might be all possible explanations for the third delay, and interested parties working on the maternal and neonatal health should prioritize overcoming these impediments.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, exposed women who were treated after half an hour (faced delay three) in the hospital were more than six times more likely to have adverse perinatal outcomes than nonexposed women (AOR = 6.40, 95% CI: 1.5–27.54). This finding is similar to studies done in Malaysia [ 30 ], Brazil [ 25 ], India [ 31 ], Mozambique [ 32 ], and Ethiopia [ 33 ] in that adverse perinatal outcomes were highly linked to third delay. This could be explained by the dearth of qualified and skilled personnel, inadequate staff, limited supply of medicine and equipment, poor facility situations, and poor attitudes and care on the part of healthcare workers which might be all possible explanations for the third delay, and interested parties working on the maternal and neonatal health should prioritize overcoming these impediments.…”
Section: Discussionsupporting
confidence: 90%
“…If a mother lacks ANC, minor obstetric conditions are not detected and managed early; therefore, serious complications and ABO will likely develop [52]. Our finding is similar to the results from Ethiopia and other LMICs, in which adverse birth outcomes, especially PTB and LBW, were higher among mothers with limited ANC visits [8,18,53]. The recommendation of eight or more ANC contacts was only introduced in 2016 by the World Health Organization (WHO) since studies at that time concluded that eight or more ANC contacts could reduce perinatal deaths by up to 8 per 1000 births when compared to only 4 visits, as previously recommended by the WHO for LMICs [54].…”
Section: Discussionsupporting
confidence: 82%
“…The most important aspect of this study for public health is that it identifies potential characteristics that predispose newborns to life-threatening conditions, which is critical to address the underlying causes and provide prompt interventions by various stakeholders in the healthcare system (74).…”
Section: Discussionmentioning
confidence: 99%